An overview of global and European photonics markets and industry: Photonics contributes to make Europe's economy more competitive and is essential to global market growth. Issue 2 (19th April 2022) - Robin, Thierry; d'Humières, Benoît; Cochard, Jacques
Abstract: The global photonics market has grown very rapidly in recent years and reached 733 billion US dollars in 2019. The European photonics industry also had a sharp increase (from € 76 B in 2015 to € 103 B in 2019), outperforming EU GDP by three times. Moreover, the global and European photonics industry has proven to be quite resilient to the effects of the Covid‐19 crisis. In fact, already present in various high‐end and next‐generation products, photonics technology has proven to be a long‐term driver of growth through its indispensable role in many current and future markets.